C.R.A.F.T. conversations for teacher growth : how to build bridges and cultivate expertise - Zepeda, Sally J., 1956-; Robinson Goff, Lakesha; Steele, Stefanie W. (ASCD, 2019)
"This engaging guide explains how administrators can elevate their conversations with teachers to enhance professional relationships, strengthen leadership and teaching, and improve student learning"--